Continuous bilateral sacral neuromodulation as a minimally invasive implantation technique in patients with functional bladder changes - Braun, Peter-Martin; Arancibia Fernández, M. Ignacio; Martínez y Portillo, Francisco-José; Seif, Christoph; Sotelino Crespo, A.; Sugimoto, S.; de Dios Montoto, E.; Alken, Peter; Jünemann, Klaus-Peter (Archivos españoles de urología, 2003)
Archivos Espanoles de Urologia 56(5): 497-501